HEPATITIS VIRUS INFECTION IN REPEATEDLY TRANSFUSED THALASSEMIA PATIENTS - Andarsini, Mia Ratwita (Institute of Topical Disease Universitas Airlangga, 2011)
Patients of thalassemia who are conventionally treated by a regular transfusion regimen, are at a risk of developing transfusion transmitted infections, including hepatitis. The present study was conducted to evaluate the prevalence of hepatitis virus infection in repeated transfused thalassemia patients. A total of 83 patients of thalassemia who had received at least 10 transfusions were tested for HBs Ag, anti HBs and anti-HCV using ELISA. Amongst these patients, HBs Ag, anti HBs and anti HBC were detected in 1.2%, 26.5% and 12% patients respectively. the prevalence of HBV and HCV infection were in agreement with the findings in other study.